AN IDENTIFICATION OF STUDENTS’ DIFFICULTIES IN PRONUNCIATION - Nikita Lasabuda (LP2M IAIN Sultan Amai Gorontalo, 2017)
This research aims to identify the difficulties of students‘ Pronunciation in 4th semester of the English Education Department of IAIN Sultan Amai Gorontalo. This research uses a qualitative method. The subject of this research is 4th semester students of English Education Department and focus of this research is on 15 Students. The location of this research is on of IAIN Sultan Amai Gorontalo. This research was conducted for 3 months with data collection technique using interview and documentation. The technique of data identification using triangulation. The results of this research indicate that pronunciation, liaisons and intonation required students to facilitate pronunciation while learning to speak in English. In this study the difficulties experienced by students in pronunciation is difficult to distinguish words that almost the same pronunciation, rarely practice in English, lack of vocabulary, often carried by local accent, shame, difficult to say sentences rarely found, nervous and less understanding of the contents of the context intended.